If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-9=3(3+x)
We move all terms to the left:
6x-9-(3(3+x))=0
We add all the numbers together, and all the variables
6x-(3(x+3))-9=0
We calculate terms in parentheses: -(3(x+3)), so:We get rid of parentheses
3(x+3)
We multiply parentheses
3x+9
Back to the equation:
-(3x+9)
6x-3x-9-9=0
We add all the numbers together, and all the variables
3x-18=0
We move all terms containing x to the left, all other terms to the right
3x=18
x=18/3
x=6
| (3x-5)+7x+5=180 | | -(6x+)=4(17-x) | | Rx10=40 | | x+4/5=(1/4)x-4/10 | | 3x+33/3=51 | | 2(3y-7)=40 | | 5(x+4)=5x+3x-1 | | 4w=138 | | 4w=136 | | 12=x10 | | 2(8-t)=5t+9 | | 2.86x=4.34 | | 3x-5=-42 | | –2x+1=13 | | 9.5x=80 | | 11(k-3)=34 | | 12=(2n-6)/4 | | x+-21=x | | 75=5v+11 | | 75=5v11 | | 75=5v1 | | n/13=4;n | | -5x+4=-42 | | 5(9-1)-4q=9 | | 3z-78=180 | | 3|m-4|=18 | | 3x-9(2+1/3x)=9 | | 7×-2y=-3 | | 2x+42=76 | | 25=4.5z+12=2.89 | | 3−–2c=9 | | y=3²+3-1 |